Immunotherapy improved cancer related pain management in patients with advanced Hepato-Pancreatic Biliary Cancers: A propensity score-matched (PSM) analysis - Wu, Xiufang; Qin, Fei; Zhang, Qiangze; Qiao, Jianling; Qi, Yulian; Liu, Bing (Frontiers in Oncology, 2022)
Background Hepato-pancreato-biliary (HPB) cancer is a serious form of cancer. in many HPB cancers, including cholangiocarcinoma (also known as bile duct cancer), pancreatic cancer, hepatocellular carcinoma, gallbladder cancer and ampullary cancer, although several treatment options are developed during these decades, the prognosis is still poor. Methods A total of 356 HPB cancers patients in advanced stage received different kinds of treatments including adjuvant chemotherapy, radiotherapy, targeted therapy and immunotherapy. Among these patients with advanced HPB cancers, 135 patients have received standard opioid treatment for pain controlling. Results We performed a PSM analysis to minimize differences between groups. Before PSM, 135 patients received standard opioid treatment for pain controlling were enrolled in this study and divided into 4 groups, including chemotherapy, radiotherapy, targeted therapy and immunotherapy. Relevant clinical variables that were available at the time of initial diagnosis were used for 1:1 matching between the two groups. After PSM, the cohort consisted of 18 patients in each group. Prior to PSM, patients received targeted therapy and immunotherapy exhibited shorter median OSs than their counterparts for patients received chemotherapy and radiotherapy (p<0.001). there were so survival differences among all the four different treatments for these patients with HPB cancers (p>0.05). We found the OMED (mg) q/day and NRS scores decreased significantly when patients received immunotherapy treatment. Fewer adverse events were showed between immunotherapy group and other three treatment groups, which was consistent with our previous reports. Conclusion In conclusion, we found that given the same survival benefit, immunotherapy reduced opioid consumption in HPB cancers patients and improved the pain management. Moreover, immunotherapy results in fewer other adverse effects.